Why Mommy swears : the struggles of an exasperated mom - Sims, Gill (HarperCollins Publishers, 2019)
It's every parents' nightmare - the start of the school holidays - and instead of sitting in the sun, reading a book over a cold, crisp glass of Pinot Grigio, Mummy has two bored moppets to attend to. After frantically booking sports camps, child minder slots, not to mention time off work, Mummy is exhausted. But this is only the beginning...--Amazon.